The story of the dinosaurs : and life on earth - Cole, Joanna; Künstler, Mort (New York, Morrow, 1974)
Describes the giant creatures who lived millions of years ago and whose fossilized bones offer the only record of their existence.
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs